Current and Future Communication Solutions for Smart Grids: A Review - Suhaimy N.; Radzi N.A.M.; Ahmad W.S.H.M.W.; Azmi K.H.M.; Hannan M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Economics; Electric power transmission networks; Network architecture; Optical communication; Optical switches; Smart power grids; Timing circuits; 'current; Communication solutions; Communicationtechnology; Networking method; Smart grid; Smart Grid Communications; Software; Two way communications; Integrated circuits